The Potentiality of the Archaic: Spinoza and the Chinese - Tatián, Diego (2014)
This essay does not set forth mainly as a study of the references that might exist within the Spinozian corpus to China, Chinese philosophy and the Chinese people in general (there is only one as far as we know, although very important, towards the end of Chapter III of the Theological-Political Treatise), nor does it focus, as its title could suggest, on the reception and circulation of Spinoza´s philosophy in China and among Chinese philosophers. It has rather two different goals. First ? taking the word ?Chinese? metaphorically as something exotic or exoptic, anything that falls out of sight, unknown and unfamiliar ? to perform a brief survey of what is strange in Spinoza´s thought: Chinese, but also Turkish and Japanese ? although leaving aside the extremely strange, like the amazons mentioned on the last page of the Political Treatise, or the enigmatic ?black and scabrous Brazilian? of the dream narrated in a letter to Pieter Balling. Next, to look into the rich and close connection established in the philosophical debates of the 17th and 18th centuries between the syntagmata ?Chinese philosophy? and ?Spinoza´s philosophy? (where intervened authors like Pierre Bayle, Nicolas Malebranche, Gottfried Wilhelm Leibniz, Christian Wolff, and later the writers of the Encyclopédie). These debates originated because of the reports and news arising from the Jesuit missions in China, starting with the texts of Mateo Ricci, who arrived to the Asian country in 1583 in order to do his early missionary work, and in particular from the texts of fathers Niccola Longobardo and Antonio de Santa María Caballero, among others.